Effect of storage on Fatty Acid Methyl Ester (FAME) and Cholesterol Oxidation Products (COPs) in different type of Sausages - Alina A.R.; Shazamawati Z.H.; Nor'Atiqah N.; Thema Juhana M.J.; Juriani J.; Syamsul K.M.W.; Siti Mashitoh A. (2024)
Indexed by Scopus